2009
DOI: 10.1063/1.3088853
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion characteristics of Al2O3 nanofluids: More to understand than understood

Abstract: In this paper, the thermal expansion characteristics of Al2O3 nanofluids have been studied and compared with the base fluid, i.e., water. The nanoparticles used were in the range of 40–80 nm, which were dispersed in water by sonication. Interestingly, it was found that the volumetric rise of the metallic oxide nanofluids is much larger than water for the corresponding temperature rise, which is opposite to what has been interpreted so far. This is one of the wonderful properties of nanofluids that would find t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
9
1
Order By: Relevance
“…Concerning the concentration dependence, first, we have found that the α p values of nanofluids are very similar to or lower than those of EG, achieving decreases up to 1.0% and 1.9% for A-TiO 2 /EG and R-TiO 2 /EG nanofluids, respectively. These results are opposite to those previously found by Nayak et al [8,9], reporting a significant increase in this property compared to the base fluid for water-based Al 2 O 3 , CuO, SiO 2 , and TiO 2 nanofluids. It should be mentioned that Nayak et al have determined the isobaric thermal expansivities by measuring the bulk variation with temperature for the samples in a glass flask with a long calibrate stem.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…Concerning the concentration dependence, first, we have found that the α p values of nanofluids are very similar to or lower than those of EG, achieving decreases up to 1.0% and 1.9% for A-TiO 2 /EG and R-TiO 2 /EG nanofluids, respectively. These results are opposite to those previously found by Nayak et al [8,9], reporting a significant increase in this property compared to the base fluid for water-based Al 2 O 3 , CuO, SiO 2 , and TiO 2 nanofluids. It should be mentioned that Nayak et al have determined the isobaric thermal expansivities by measuring the bulk variation with temperature for the samples in a glass flask with a long calibrate stem.…”
Section: Resultscontrasting
confidence: 99%
“…Hence, it is often presumed that this coefficient should decrease with rising concentration of nanoparticles as we have previously reported [10]. Nevertheless, some works [8,9] have found the opposite behavior of the one resulting from considering the fluids to behave separately in the mixture for the case of water-based Al 2 O 3 nanofluids. This is one of the singular properties of nanofluids that would find a remarkable application in many heat extraction systems using natural convection as a heat removal method [11].…”
Section: Reviewmentioning
confidence: 68%
See 2 more Smart Citations
“…As the particle concentration increases, effective density of the nanofluid is enhanced and specific heat, C p , is reduced. By suspending the nanoparticles in the base fluid, the net specific heat of the nanofluid is reduced [16] as well as thermal expansion coefficient, β, of the nanofluid is increased [17] and hence the temperature of loop fluid increases for the same heat input. In the simulation, the specific heat of Al 2 O 3 -water nanofluid is estimated using the eq.…”
Section: Steady-state Flow Ratementioning
confidence: 99%